Dual-Core Liquid Filled Photonic Crystal Fiber Coupler - Hossain, Md Bellal; Hossain, Md Mahbub; Rahaman, Md Ekhlasur; Ali, Md Younus; Shekhar Mondal, Himadri (International Journal of Engineering and Technology, 2018)
Photonic crystal fiber coupler (PCFC) is one of the remarkable devices that contribute a key responsibility in passive optical networks and enormous optical systems. This paper presents a dual-core liquid filled PCFC with rectangular and hexagonal geometry for analyzing different guiding properties from 1200 to 1800 nm wavelength range by finite difference time domain (FDTD) method with transparent boundary condition (TBC). In the proposed design, the background material (Silica and BK7) and the liquid (water, chloroform, benzene) in the dual-core are varied. Results imply very small confinement loss with low coupling length for wide wavelength range. At 1.55 µm wavelength, hexagonal PCFC (Silica) shows 0.00025, 0.00051, and 0.00095 m coupling length for water, chloroform, and benzene infiltrated dual-core, respectively. As well, the confinement loss of 1.655×10−8, 0.84×10−8, and 0.739×10−8 dB/km and the birefringence of 3.08×10−4, 1.48×10−4, and 0.801×10−4 are obtained in water, chloroform, and benzene filled dual-core, correspondingly. Furthermore, at 1.55 µm wavelength benzene exhibits the maximum polarization-insensitivity for the both the PCFC structures. In addition, the proposed PCFCs demonstrate high coupling coefficient with ultra flattered dispersion for broad wavelength range.
Keywords: Birefringence; Coupling length; Confinement loss; Photonic crystal fiber coupler (PCFC); Polarization-insensitivity; Propagation constant.